Foreign and Intratrade Policies of Arab Countries - El-Naggar, Said. (Washington, D.C. : International Monetary Fund, 1992)
The challenge facing the Arab countries to maintain economic growth in the face of the deteriorating terms of trade affecting all developing countries was addressed in a seminar held in Abu Dhabi in early 1992. This volume, edited by Said El-Naggar, includes papers by contributors from the region as well as from the IMF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet